Queer Clout Chicago and the Rise of Gay Politics - Stewart-Winter, Timothy (Politics and Culture in Modern America, 2015)
In postwar America, the path to political power for gays and lesbians led through city hall. By the late 1980s, politicians and elected officials, who had originally sought political advantage from raiding gay bars and carting their patrons off to jail, were pursuing gays and lesbians aggressively as a voting bloc—not least by campaigning in those same bars. Gays had acquired power and influence. They had clout.Tracing the gay movement's trajectory since the 1950s from the closet to the corridors of power, Queer Clout is the first book to weave together activism and electoral politics, shifting the story from the coastal gay meccas to the nation's great inland metropolis. Timothy Stewart-Winter challenges the traditional division between the homophile and gay liberation movements, and stresses gay people's and African Americans' shared focus on police harassment. He highlights the crucial role of black civil rights activists and political leaders in offering white gays and lesbians not only a model for protest but also an opening to join an emerging liberal coalition in city hall. The book draws on diverse oral histories and archival records spanning half a century, including those of undercover vice and police red squad investigators, previously unexamined interviews by midcentury social scientists studying gay life, and newly available papers of activists, politicians, and city agencies.As the first history of gay politics in the post-Stonewall era grounded in archival research, Queer Clout sheds new light on the politics of race, religion, and the AIDS crisis, and it shows how big-city politics paved the way for the gay movement's unprecedented successes under the nation's first African American president